Incorporação imobiliária e verticalização em Uberlândia-MG: expansão, desafio e futuro - Lomolino, Ana Laura Gonçalves (2024)
The real estate market is one of the most expressive and important business sectors in the Brazilian economy, contrary to most economic sectors that reduced or stopped their growth during the peak of the COVID-19 pandemic in Brazil, the real estate market remained heated and even with the increase in input values, it showed considerable growth. In this context, the city of Uberlândia in the Triângulo Mineiro region - Minas Gerais, with significant importance for the state's economy, has been consolidating even more in recent decades, this process has one of its expansion fronts in the real estate market. Therefore, understanding how this dynamic occurred in its origins and what effects were felt after 2015, a period in which the municipality began to receive significant investments from developers from other states, is also one of the ways of understanding the reproduction of urban space in the city. Since the time frame defined by this research, the city has been receiving significant investments from developers from states such as São Paulo and Brasília, which has changed the service options delivered by the projects, with one of its consequences being the creation of a new urban landscape. in the city, mainly in the south and east zones, which consequently increases the prices charged. With the arrival of new developers in the city, combined with the ease of negotiation for the acquisition of projects, in addition to the high volume of launches, creating a high stock of launched units, our research hypothesis is that the real estate agents who guide the implementation and execution of architectural housing projects aimed at high incomes in the city has been creating new Skylines in the city, breaking with the production of horizontal properties. Thus, the use of urban space carried out by such agents in the urban context has significantly changed the use of land in the city. To do this, we will analyze four developers who were selected after a survey and methodological analysis where we observed the volume of launches since their arrival in the city and/or foundation, the importance of their products in the local market, the impact on changing the urban landscape where they are concentrated, in addition to the high value of salable square meters, they are: Brasal Incorporações, Bild Desenvolvimento Imobiliário, Persa Incorporações and Idealiza Cidades.